2016
DOI: 10.1016/j.jad.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diagnosed depression on healthcare costs in adults with and without diabetes: United States, 2004–2011

Abstract: Objective This study used the Medical Expenditures Panel Survey (MEPS) to estimate the cost of diabetes, depression, and comorbid diabetes and depression over 8 years. Methods An 8-year pooled dataset was created using the household and medical provider components of MEPS. Medical expenditures were adjusted to a common 2014 dollar value. Analyses used responses of 147,095 individuals ≥18 years of age for the years 2004–2011. The dependent variable in this study was total healthcare expenditure and the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 33 publications
4
40
0
Order By: Relevance
“…The comorbidity between depression and diabetes leads to significant adverse outcomes such as less adequate glycemic control (Lustman, Anderson, Freedland, de Groot, & Carney, 2000;GDB 2016Risk Factor Collaboration, 2016; more diabetic complications (GDB 2016Risk Factor Collaboration, 2016; increased service use, and lower medication adherence (Ciechanowski, Katon, Russo, & Hirsch, 2003;Egede, Bishu, Walker, & Dismuke, 2016;Gonzalez et al, 2008). The mortality risk in patients with comorbid depression and diabetes is higher than expected by each condition alone (Katon et al, 2008;Park, Katon, & Wolf, 2013; van Dooren et al, 2013;GBD 2017Causes of Death Collaborators, 2017.…”
Section: Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…The comorbidity between depression and diabetes leads to significant adverse outcomes such as less adequate glycemic control (Lustman, Anderson, Freedland, de Groot, & Carney, 2000;GDB 2016Risk Factor Collaboration, 2016; more diabetic complications (GDB 2016Risk Factor Collaboration, 2016; increased service use, and lower medication adherence (Ciechanowski, Katon, Russo, & Hirsch, 2003;Egede, Bishu, Walker, & Dismuke, 2016;Gonzalez et al, 2008). The mortality risk in patients with comorbid depression and diabetes is higher than expected by each condition alone (Katon et al, 2008;Park, Katon, & Wolf, 2013; van Dooren et al, 2013;GBD 2017Causes of Death Collaborators, 2017.…”
Section: Riskmentioning
confidence: 99%
“…There is a large body of literature suggesting a bidirectional association between depression and diabetes, and the comorbidity between these 2 conditions is high (Diniz, Fisher‐Hoch, & McCormick, , Holt et al, , Katon et al, , Korczak, Pereira, Koulajian, Matejcek, & Giacca, , Moulton et al, , Vancampfort et al, ). The comorbidity between depression and diabetes leads to significant adverse outcomes such as less adequate glycemic control (Lustman, Anderson, Freedland, de Groot, & Carney, ; GDB Risk Factor Collaboration, 2016); more diabetic complications (GDB Risk Factor Collaboration, 2016); increased service use, and lower medication adherence (Ciechanowski, Katon, Russo, & Hirsch, ; Egede, Bishu, Walker, & Dismuke, ; Gonzalez et al, ). The mortality risk in patients with comorbid depression and diabetes is higher than expected by each condition alone (Katon et al, ; Park, Katon, & Wolf, ; van Dooren et al, ; GBD Causes of Death Collaborators, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the presence of depression more than doubled the annual per person total healthcare costs, a number of missed work days and lost wages due to missed work days, even after controlling for predisposing factors, enabling characteristics, need factors, and personal health care practices. Although published evidence on the incremental economic impact of depression in RA is limited81 , our findings are consistent with studies assessing the burden of depression on other chronic illness such as diabetes, cardiovascular disease and asthma have also reported the synergistic effect of depression in increasing the economic burden among individuals with chronic conditions76,95 .Our findings on the economic burden of depression in RA patients has important implications for the payers as it highlights an opportunity for reducing expenditures in RA patients by increasing efforts towards screening and effectively treating depression in RA patients. Potential strategies such as improving the integration of mental health services with rheumatology practice and facilitating mental health training for rheumatologists.…”
supporting
confidence: 88%
“…[12][13][14] Recently, the Research Aimed at Improving Both Mood and Weight (RAINBOW) trial reported that an integrated collaborative care intervention, as compared with usual care, led to significantly improved weight loss and depressive symptoms through 12 months among primary care patients of both sexes who had obesity and depression. [14] Similar to prior trials showing effectiveness of behavior therapy in either of these conditions alone [15][16][17][18] or in related multiple chronic conditions-such as depression and diabetes or under a formal data sharing and use agreement that provides for a commitment to the following: (1) using the data only for research purposes and not to identify any individual participant, (2) securing the data using appropriate computer technology, which needs to be specified, (3) destroying or returning the data after analyses are completed, (4) accepting reporting responsibilities, (5) abiding by restrictions on redistribution of the data for commercial purposes or to third parties, and (6) proper acknowledgement of the data resource. Data sharing request shall be submitted to the Institutional Review Board for the University of Illinois at Chicago whose contact information is below.…”
Section: Introductionmentioning
confidence: 97%
“…Obesity and depression are highly prevalent in the United States with associated high personal and societal cost. [1,2] Currently among US adults, nearly 40% are obese [3] and 19% experience major depression over the course of their lifetime. [4] Subthreshold depression is also common, with increased burden of morbidity and disability.…”
Section: Introductionmentioning
confidence: 99%